2018
DOI: 10.3399/bjgp18x695465
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of multimorbidity in primary care: a retrospective cohort study

Abstract: BackgroundMultimorbidity places a substantial burden on patients and the healthcare system, but few contemporary epidemiological data are available.AimTo describe the epidemiology of multimorbidity in adults in England, and quantify associations between multimorbidity and health service utilisation.Design and settingRetrospective cohort study, undertaken in England.MethodThe study used a random sample of 403 985 adult patients (aged ≥18 years), who were registered with a general practice on 1 January 2012 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
432
5
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(507 citation statements)
references
References 16 publications
24
432
5
12
Order By: Relevance
“…Regardless, implementing different schemes and guidelines for each group is unduly complex and inefficient, especially as they share several core management elements (medicines review, personalised assessment, care planning). In addition, more than 25% of adults have two or more chronic conditions,18 hence the multimorbidity guidelines require additional factors to be present such as frailty, risk for unplanned care, or management complexity,17 further blurring distinctions between the groups. Although frailty is the more complex concept, it has a strong theoretical basis related to its origins in geriatric medicine 19…”
Section: Challenges To Adopting the Frailty Agenda In Primary Carementioning
confidence: 99%
“…Regardless, implementing different schemes and guidelines for each group is unduly complex and inefficient, especially as they share several core management elements (medicines review, personalised assessment, care planning). In addition, more than 25% of adults have two or more chronic conditions,18 hence the multimorbidity guidelines require additional factors to be present such as frailty, risk for unplanned care, or management complexity,17 further blurring distinctions between the groups. Although frailty is the more complex concept, it has a strong theoretical basis related to its origins in geriatric medicine 19…”
Section: Challenges To Adopting the Frailty Agenda In Primary Carementioning
confidence: 99%
“…The study, published in the British Journal of General Practice ,1 found that over a third of people with multimorbidities also had a mental health condition. Helen Stokes-Lampard, college chair, said that the research was “further evidence of the increasing complexity of cases that GPs are dealing with, and the inadequacy of the standard 10 minute consultation.”…”
Section: Nhs Pressuresmentioning
confidence: 99%
“…Recent UK data shows that 23-27% of people have two or more conditions and their care needs account for over 50% of primary and secondary care costs and a substantial portion of community and social care costs. [1] [2] [3] Trials of initiatives to improve outcomes and reduce emergency secondary care use of those with multimorbidity have not shown immediate success. [4] [5] Therefore, more is needed to understand the drivers of care use and costs for those living with multimorbidity, and identify ways their care could be improved.…”
Section: Introductionmentioning
confidence: 99%
“…This list was adapted from[1]. A list of Read codes and Gemscript codes is available at http://www.phpc.cam.ac.uk/pcu/cprd_cam/codelists/Supplementary Table 4.…”
mentioning
confidence: 99%